Doubly excited (v4=2) vibrational state of 12CH2 35 Cl2: Centrifugal distortion and quadrupole splittings in the submillimeter wave spectra up to 1.1 THz; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 346 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Nikolaeva V. E. Valeriya Evgenjevna; Gorbacheva E,. D. Ekaterina Dmitrievna (2025, 2025)
Title screen